Blessings beyond the binary: Transparent and the queer Jewish family - Rubel, Nora L.; Krutzsch, Brett (Rutgers University Press, 2024)
"Transparent made history as the first television show to feature a transgender character in the main role, as the first streaming series to win the Golden Globe for Best Television Series, and as, in the words of journalist Debra Nussbaum Coen, "the Jewiest show ever." No television show in history has depicted the lives of American Jews with as much attention to Jewish rituals, quirks, or culture. And no series has portrayed issues of gender and sexuality alongside Judaism with such nuance and depth, making Transparent a landmark series in the history of television. Blessings Beyond The Binary: Transparent and the Queer Jewish Family brings together leading scholars to analyze and offer commentary on what scholar Josh Lambert calls, "the most important work of Jewish culture of the century so far". The book explores the show's depiction of Jewish life, religion, and history, as well as Transparent's scandals, criticisms, and how it fits and diverges from today's transgender and queer politics. The first book to focus on Transparent, Blessings Beyond the Binary offers a rich analysis of the groundbreaking series and its connections to contemporary queer, trans, and Jewish life"--